LINGUISTIC AND CULTURAL ANALYSIS OF THE PHRASEOLOGY OF THE ENGLISH LANGUAGE - Shakhnozakhon Ismatova (Journal of new century innovations, 2023)
Abstract. At present, special attention is paid in the cognitive linguistics to the problem of linguistic units that represent different knowledge structures. Phraseological units, being one of the core linguistic means of verbalization of different knowledge structures, are ought to be analyzed thoroughly. Further to this, idiomatic expressions and proverbs are vital signals in verbalization of cultural values and national specific concepts which leads to the necessity of linguo-cultural analysis of these units. This article is aimed to analyze phraseological units with the fire component in English language according to cultural and cognitive parameters and to identify cultural values and cognitive models that are presented by these expressions.